Surveillance of ochratoxin A in cocoa beans from cocoa-growing regions of Ghana - Joel Cox Menka Banahene; Isaac Williams Ofosu; Bernard Tawiah Odai (Heliyon, 2023)
Cocoa is one of the agricultural commodities which is highly susceptible to mycotoxin contamination. During two crop/harvest seasons, the occurrence and distribution of ochratoxin A (OTA) in viable commercial cocoa beans were investigated. The cocoa bean samples were collected randomly from farmers across cocoa-growing regions of Ghana. OTA concentrations in the samples were determined by liquid chromatography-tandem mass spectrometry (LC-MS/MS) methods following purification on immunoaffinity solid phase column. The result showed that 21.7% of all samples analyzed were contaminated with OTA at concentrations ranging from 0.01 μg/kg to 12.36 μg/kg. The Western South region had the highest occurrence of OTA-positive samples at 32.5%, followed by the Western North region at 28.75%, the Eastern and Volta regions at 25% each, Brong Ahafo (16.25%), Central (15%) and the Ashanti region at 11.25%. However, 0.9% and 3.5% of the total OTA-positive samples exceeded the OTA maximum limits of 10 μg/kg for cocoa beans and 3 μg/kg for cocoa powder, set by the Brazilian National Health Surveillance Agency and the European Commission, respectively. During the Main and Light crop seasons, the highest concentrations of OTA were detected in the Western North region, reaching up to 12.36 μg/kg and 3.45 μg/kg, respectively. OTA concentrations between the cocoa-growing regions in the Main crop season were not significantly different (p > 0.05), however, the Light crop season indicated a significant difference (p < 0.05). There was a significant difference (p < 0.05) between the two crop seasons. The need for regular monitoring and careful adherence to agronomic strategies such as good agricultural practices (GAPs), recommended code of practices (COPs) and good manufacturing practices (GMPs) for the prevention and reduction of OTA throughout the cocoa value chain cannot be overemphasized.